Iran before the Security Council? German perspectives and goals - Oliver Thränert (Stiftung Wissenschaft und Politik (SWP), 2006)
Germany and its partners would like to see the Iranian nuclear program referred to the United Nations Security Council. This would bring new momentum into the protracted conflict over Tehran's nuclear projects. The goal is to give the demand for suspension of uranium enrichment in Iran proper backing at the highest international level, while at the same time avoiding escalation. This can only succeed if the Europeans stick together and the transatlantic alliance holds. What is Iran actually accused of? What were France, Britain, and Germany - the EU-3 group - aiming at in their negotiations with Iran and what have they achieved? How should the Security Council proceed? (SWP-Comments / SWP)
Keywords: 320